The Interactional Effect of Modeling (Skilled and Self-Model) and Feedback on Performance and Learning of Dart Throwing Skill - Abolfazl Shayan; Davood Homeniyan; Hossein AbediniParizi; Jamal Fazel Kalkhoran (University of Tehran, 2012)
The aim of this study was to determine the interactional effects of various video shows (skilled and self-model) and feedback type on performance and learning of dart throwing skill. 90 volunteers were randomly divided into 6 groups including self-control, experimenter control and yoked feedback that received either skilled model or self-model. Three groups who watched the skilled model observed dart throwing by a member of dart national team at first and at rest intervals whereas self-model groups watched their own performance as a recorded movie. Selfcontrol groups requested feedback from the examiner during their performance. Yoked groups received feedback in those attempts on which self-control groups requested feedback and experimenter-control groups received feedback by examiner. Subjects trained for six days and then participated in the retention (after 48 hours) and transfer (immediately after retention) tests. The method of the study was semi-experimental and data were analyzed using analysis of variance with repeated measures, two-way analysis of variance and Bonferroni and Tukey post hoc tests. Results showed that all six groups improved from pretest to acquisition, retention and transfer. Regardless of the role of feedback, there was no difference between skilled and self-model in any stages. Experimenter control feedback had more efficiency than other feedbacks in the acquisition while self-control feedback was better in retention and transfer. Furthermore, results showed that those subjects who received self-control feedback had more learning when they observed self-model. The main reason why self-model-self-control feedback group was better than other groups could be the effect of motivational processes resulted from this interaction and more coordination of this feedback with subjects' demands.